2016
DOI: 10.1007/s00417-016-3417-8
|View full text |Cite
|
Sign up to set email alerts
|

Central serous chorioretinopathy in primary hyperaldosteronism

Abstract: PurposeTo describe ophthalmological characteristics of 13 patients with primary hyperaldosteronism (PA).MethodsCross-sectional study. All patients underwent extensive ophthalmological examination.ResultsThirteen PA patients (9 male, 4 female) were diagnosed with arterial hypertension for 11.0 ± 11.2 years. Ophthalmological imaging revealed macular serous subretinal fluid (SRF) on optical coherence tomography in 2 patients (15 %). In one of these patients, bilateral chronic central serous chorioretinopathy (CSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…reported that retinal abnormalities resembling central serous chorioretinopathy were frequently observed in PA patients, and speculated the potential involvement of the mineralocorticoid receptor-mediated pathway in the pathogenesis of the disease [8]. In our present cases, no eyes showed any apparent fundus abnormalities indicative of central serous chorioretinopathy.…”
Section: Plos Onesupporting
confidence: 63%
“…reported that retinal abnormalities resembling central serous chorioretinopathy were frequently observed in PA patients, and speculated the potential involvement of the mineralocorticoid receptor-mediated pathway in the pathogenesis of the disease [8]. In our present cases, no eyes showed any apparent fundus abnormalities indicative of central serous chorioretinopathy.…”
Section: Plos Onesupporting
confidence: 63%
“…In particular, MR receptor pathway activation causes choroidal vasodilation and leakage, due to upregulation of the vasodilator potassium channel KCa2.3 (calciumdependent channel) and smooth muscle cells relaxation in the choroidal vasculature [66]. These evidences have also been supported by ophthalmologic findings within patient with primary hyperaldosteronism [67].…”
Section: Mineralocorticoid Receptor (Mr) Antagonistsmentioning
confidence: 84%
“…Furthermore, the finding of CSC(-like) changes in primary hyperaldosteronism indicate a role for the MR in the pathogenesis of CSC. 11 Zhao et al 12 have proposed an underlying mechanism of this association: aldosterone could lead to transcriptional upregulation of the endothelial vasodilatory potassium channel KCa2.3, and blockade of this channel prevents aldosterone-induced choroidal thickening (pachychoroid), 38 which is typical for CSC and which has led to the introduction of MR antagonists for CSC in clinical practice. Nonetheless, the variation in the KCa2.3 channel was very small at the protein level, suggesting the involvement of other mechanisms in inducing the observed choroidal changes in the rat model.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Because corticosteroids bind to both the glucocorticoid receptor (GR) and the mineralocorticoid receptor (MR), it has been hypothesized that both are involved in the pathogenesis of CSC. 5,[9][10][11][12] Because of the plausible role of the choroidal endothelium in the pathophysiology of CSC, culturing of human choroidal endothelial cells (CECs) is of particular interest. [13][14][15][16] Endothelial cells (ECs) are heterogenic cells that show substantial sitespecific structural and biochemical variation due to their interaction with their surroundings.…”
Section: Conclusion With This Optimized Choroidal Endothelial Cell mentioning
confidence: 99%